Analysis of Child Exploitation Cases According to Law 35 of 2014 concerning Child Protection (Case Study of Supreme Court Decision Number (58/Pid. Sus/2013/PN Pti) - Ivana Trixie; Rasji Rasji (CV. Rayyan Dwi Bharata, 2023)
According to the Provisional Population Projection Results for 2022–2023 published by the Central Statistics Agency, there are 94,377.6 children between the ages of 0 and 19. Children are a responsibility and a gift from God Almighty that must be preserved since children are born with intrinsic human dignity. Children under the age of 18 are supposedly prohibited from understanding what labor is. The responsibility of the kid is to obtain the right to education and instruction in order to advance their level of intelligence and in line with their interests and abilities.